Pityriasis rosea recurrence is much higher than previously known: A prospective study - Yüksel, Mavişe (Acta Dermato-Venereologica, 2019)
Pityriasis rosea is a common acute exanthema of unknown aetiology, which causes severe anxiety. In this study, the demographic data of pityriasis rosea patients, who presented to our clinic between 2013 and 2017, were prospectively recorded. The patients with a confirmed pityriasis rosea diagnosis were followed up for 4 years in order to investigate the recurrence rate. Of the clinically suspected patients, having a typical history of pityriasis rosea manifestations, a herald patch, and/or secondary coloured squamous lesions, 400 were confirmed by biopsy to have pityriasis rosea. The 4-year follow-up was completed in 212 patients, of whom 136 (64.2%) were female and 76 (35.8%) were male. The recurrence rate was determined as 25.9% at the end of the 4-year follow-up period.
WOS: 000470074900006
PubMed ID: 30848285
Keywords: Pityriasis Rosea; Recurrence; Prospective Studies